Molecular hybridization yields triazole bronchodilators for the treatment of COPD - Jones, Lyn H.; Burrows, Jane; Feeder, Neil; Glossop, Paul; James, Kim; Jones, Rhys M.; Kenyon, Amy S.; Patel, Sheena; Roberts, Dannielle F.; Selby, Matthew D.; Strang, Ross S.; Stuart, Emilio F.; et al. (Bioorganic & medicinal chemistry letters, 2015)
[Display omitted] A 1,2,4-triazole motif was employed as a bioisostere for the ester commonly used in muscarinic antagonists, and subsequent integrative conjugation to a β2 agonist quinolinone furnished a new class of bifunctional MABAs for the treatment of COPD. Medicinal chemistry optimization using the principles of ‘inhalation by design’ furnished a clinical candidate with desirable pharmacological, pharmacokinetic and biopharmaceutical properties.